2008
DOI: 10.1111/j.1540-8191.2008.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

The Right Gastroepiploic Artery in Coronary Artery Bypass Grafting

Abstract: The right gastroepiploic artery (RGEA) has been used as a conduit in coronary artery bypass grafting. Although some reports presenting good results justify its use in clinical settings, there is still much concern about using the RGEA in bypass surgery. The RGEA demonstrates different behaviors from the internal thoracic artery (ITA) in bypass surgery due to its histological characteristics and anatomical difference, which might contribute to the long-term outcome. Now that left ITA (LITA) to left anterior des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…Moreover, it has also been recently confirmed that the GEA can be used as a Y graft and then anastomosed to circumflex territory [21 ], albeit there are controversial reports about the patency rates: whereas Ryu et al [15] reported excellent results, Santos et al [22] described a poor patency rate of the LIMA-GEA grafts when compared with the LIMA-radial artery grafts. Therefore, as a Y graft, the GEA could be used in specific subsets of patients, such as diabetic, obese, with COPD (not suitable for bilateral IMA harvesting) or with renal insufficiency, positive Allen test, or radial artery calcifications.…”
Section: Choosing the Proper Arterial Conduitsmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, it has also been recently confirmed that the GEA can be used as a Y graft and then anastomosed to circumflex territory [21 ], albeit there are controversial reports about the patency rates: whereas Ryu et al [15] reported excellent results, Santos et al [22] described a poor patency rate of the LIMA-GEA grafts when compared with the LIMA-radial artery grafts. Therefore, as a Y graft, the GEA could be used in specific subsets of patients, such as diabetic, obese, with COPD (not suitable for bilateral IMA harvesting) or with renal insufficiency, positive Allen test, or radial artery calcifications.…”
Section: Choosing the Proper Arterial Conduitsmentioning
confidence: 93%
“…Therefore, as a Y graft, the GEA could be used in specific subsets of patients, such as diabetic, obese, with COPD (not suitable for bilateral IMA harvesting) or with renal insufficiency, positive Allen test, or radial artery calcifications. It should be stressed that the use of the GEA is not feasible in patients with previous abdominal surgery and should be carefully elected in patients at potential risk for abdominal surgery [21 ].…”
Section: Choosing the Proper Arterial Conduitsmentioning
confidence: 99%
“…[2][3][4][5] Other autologous arterial/venous grafts, cryopreserved cadaveric grafts, umbilical vein grafts, and arterial allografts have also been tried but with limited success because of associated complications. [6][7][8][9][10][11] Although autologous vessels from patients remain the grafts of choice, in many cases, previous harvest, morbidity at the donor site, or disease progression limit the availability of native grafts. 12,13 Clinical studies suggest that only a limited number of patients undergoing CABG surgeries have suitable arterial grafts and up to 30% of patients requiring venous grafts for peripheral vascular diseases lack transplantable veins.…”
Section: Vascular Tissue Engineering: Unmet Clinical Needmentioning
confidence: 99%
“…Since the introduction of the right gastroepiploic artery (RGEA) as a graft in coronary artery bypass grafting (CABG) by Pym [1] and Suma [2] in 1987, it has been widely used as a graft in coronary artery bypass grafting because it is ease to harvest and has a lower morbidity related to surgery [3]. The RGEA graft also has a high clinical availability for coronary artery bypass grafting [4], low incidence of arteriosclerosis [5], and sufficient flow capacity [6].…”
Section: Introductionmentioning
confidence: 99%